To Study the Impact of Language and Social Development on Children When Using a Gadget - Esnazarova Zulfiya Oljabaevna (Genius Journals, 2022)
Because of the rapid technological advancements that have resulted in the development of a wide range of functions and features, devices are now utilized not only by adults, but also by younger children. With a variety of intriguing features, they can encourage children to become consumers of consumer electronics at a young age. The device is said to have a negative impact on children's development, as it can stifle language and social development. When children use the gadgets they have to play games, watch videos, and so on, it takes time away from them playing and socializing with their peers, and it also prevents them from developing language. On the other hand, the gadget could have a positive impact on the child's development. This article discusses about the impact of language and social development on children when using a gadget.
Keywords: Study; Language Development; Social Interaction; Chidren